GIS-material for the archaeological project: Borgmästaregatan street and others - Expansion of the sewer system - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
The preliminary investigation was performed as an archaeological inspection, due to rebuilding of the sewer system on the streets around the Banken block, located at the medieval centre of the city of Linköping. Five small trenches and a larger one were excavated along Borgmästaregatan street. The larger trench in the south part of the street was excavated in an area of great interest and of great importance to the medieval city, since it includes, among other things, the Saint Lars graveyard, the boundaries of several building lots and an earlier discovered alley. The relation between these features is of great importance to understand and analyse the establishment and development of the earliest stages of the city. Unfortunately, it turned out that the trenches were excavated in mostly disturbed layers. Only small parts of undisturbed cultural layers could be documented in the south part, but these were far too fragmentary to be able to contribute to the area's history.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the preliminary investigation was to determine whether there were any preserved cultural layers, and, if possible, to get a more detailed picture of what is earlier known about the area. It was also of great importance to examine the stratigraphic relations between the various building lots, the old alley, the Saint Lars graveyard and an earlier discovered layer of limestone chips.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Förundersökningen skedde i form av en antikvarisk kontroll och föranleddes av renovering av VA-nätet i gatorna runtom kv Banken i centrum av det medeltida Linköping. Till stor del skedde arbetet genom att fem mindre schakt samt ett längre i Borgmästaregatans nedre del togs upp. Det längre schaktet i söder har ett mycket intressant läge i en viktig del av den medeltida staden Linköpings historia, då den berör bl a S:t Larskyrkans kyrkogård, samt flera tomtgränser och en gränd som påträffats vid tidigare tillfällen. Relationen mellan dessa är av stor betydelse för att kunna förstå och analysera det äldsta Linköpings etablering och framväxt. Det visade sig dock att schakten till stora delar gick i omrörda lager. Endast mindre partier av orörda kulturlager kunde dokumenteras i södra delen, men dessa var alltför fragmentariska för att kunna bidra till områdets historia.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Målsättningen med förundersökningen var att konstatera om det fanns bevarade kulturlager eller ej och om möjligt fördjupa den tidigare kunskapsbilden. Den stratigrafiska relationen mellan olika tomtgränser, en äldre gränd, S:t Lars kyrkogård samt en tidigare påträffad kalkflisläggning är av största vikt.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Borgmästaregatan m fl - VA-utbyggnad
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi